Isolated penile Kaposi's sarcoma in a HIV-positive patient stable on treatment for three years. (July 2014) - Lebari, Dornubari; Gohil, Jesal; Patnaik, Lipsita; Wasef, Wafaa
Kaposi's sarcoma (KS) is an AIDS-defining condition. Typically, KS affects the skin with or without visceral involvement. The extensive use of antiretroviral therapy (ART) has decreased the incidence of KS amongst the HIV-positive population. We report a case of a 40-year-old man with HIV-1 infection with CD4 count of 551 cells/mm 3 and an undetectable viral load who presented with two skin-coloured KS lesions on the prepuce of the penis. Diagnosis was confirmed by histopathology. He had been commenced on ART three years earlier with a nadir CD4 count of 255 cells/mm 3 . He had achieved and maintained viral suppression since commencing ART. The patient was initially treated with cryotherapy and 5% imiquimod as the lesions were presumed to be warts. The lack of response to treatment prompted further investigation. We carried out a literature search of published cases of penile KS over the past 10 years. The majority of articles regarding penile KS were published in the pre-ART era and involved patients with AIDS. Over the past 10 years, published cases of penile KS have almost exclusively been in HIV-negative men. We found 10 published cases of penile KS in HIV-negative men and only one other published case of penile KS in a HIV-positive man, who had severe immune suppression with CD4 count below 200 cells/mm 3 . This is the first case report to describe a HIV-positive patient stable on ART with a CD4 count above 200 cells/mm 3 and suppressed HIV-1 viral load, to develop two KS lesions on the penis. Clinicians have to remain suspicious of penile lesions and appreciate the crucial role a biopsy with histopathological analysis plays in confirming a diagnosis. In addition, this case illustrates that unusual presentations of KS can still occur in treated HIV-positive patients with sustained immune recovery.